Integrating the Values of Islam Rahmatan lil ‘Alamin into Learning Practices in Madrasah Tsanawiyah - Sholikhah, Virdatus; Aini, Nurul; Noviani, Dwi (International Journal on Advanced Science, Education, and Religion, 2025)
This study aims to analyze the forms and strategies of integrating the values of Islam Rahmatan lil ‘Alamin (Islam as a mercy for all creation) in the learning process at Madrasah Tsanawiyah. Islam Rahmatan lil ‘Alamin emphasizes the principles of compassion, justice, tolerance, and balance in life. In the context of Islamic education, these values are essential to be internalized so that students not only gain knowledge but also develop noble character and a moderate attitude in practicing their faith. This research employs a qualitative descriptive approach with data collected through classroom observation, teacher interviews, and document analysis. The results indicate that the integration of Rahmatan lil ‘Alamin values is implemented through: (1) thematic learning that links lesson content with universal Islamic values; (2) teachers’ exemplary attitudes and behavior; and (3) habituation of good morals through religious activities in the madrasah. The implications of this study highlight that Islamic education plays a strategic role in shaping a generation that is knowledgeable, moderate, and possesses commendable character.